2022
DOI: 10.48550/arxiv.2203.06878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contribution of the Weinberg-type Operator to atomic and nuclear electric dipole moments

Naohiro Osamura,
Philipp Gubler,
Nodoka Yamanaka

Abstract: The contribution of the CP violating three-gluon Weinberg operator, 1 3! w f abc νραβ G a µν G b αβ G cµ ρ , to the atomic and nuclear EDMs is estimated using QCD sum rules. After calculating the transition matrix element between the pion and the vacuum through the Weinberg operator, we obtain the long-range CP-odd nuclear force by determining the isovector CP-odd pion-nucleon vertex, using chiral perturbation theory at NLO. The EDMs of 199 Hg, 129 Xe, 225 Ra, 2 H, and 3 He are finally given including compreh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 150 publications
(228 reference statements)
0
8
0
Order By: Relevance
“…We also note that the one-pion exchange process [Fig. 2 (c)], which is a priori subleading in χEFT, was found to not be negligible for heavy atoms through QCD sum rules calculation [113]. The reducible contribution may be evaluated like the nucleon EDM, by chirally rotating the CP-even contact interaction L N N = − 1 2 C S N N N N with C S = −120.8 GeV −2 obtained from χEFT analysis [114].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…We also note that the one-pion exchange process [Fig. 2 (c)], which is a priori subleading in χEFT, was found to not be negligible for heavy atoms through QCD sum rules calculation [113]. The reducible contribution may be evaluated like the nucleon EDM, by chirally rotating the CP-even contact interaction L N N = − 1 2 C S N N N N with C S = −120.8 GeV −2 obtained from χEFT analysis [114].…”
Section: Introductionmentioning
confidence: 94%
“…( 2). For heavy nuclei, the one-pion exchange CP-odd nuclear force generated by the WO also becomes important, and it may in some cases be comparable to the nucleon EDM effect [113,170,171]. This process is also currently affected by a large uncertainty.…”
Section: Edm Of 3 He Nucleusmentioning
confidence: 99%
See 2 more Smart Citations
“…This operator was first calculated in the Higgs doublet model [7], and then, it has been found that some other models also generate it such as the supersymmetric model [8]. While the relation between this operator and the neutron EDM has been investigated widely [9,10,11], its value for the CP-odd nucleon-nucleon (N N ) interaction, which is expected to give the main contribution to the atomic EDMs, has only been evaluated quite recently [12,13].…”
Section: Introductionmentioning
confidence: 99%